(DE)(RE)territorializing re-entry adult learners. (9th September 2022) - Kokorudz, Shelley
Abstract: This article describes a posthuman study that used Deleuze's rhizoanalysis to explore the journeys of adult learners who returned to an adult high school to pursue their high school diplomas after having prematurely left high school. Five graduated adult students participated in individual recorded intra-views, and two of them also participated in a small group discussion with the researcher to speak of their journeys. The (non)data were cartographically created to map the intra-active complexities that (de)(re)territorialize re-entry adult learners. As the assemblages were mapped, participants were decentred and material world experiences were extended. Common notions around dropout students were disrupted, and re-entry processes for adult learners were (re)thought as new problems and questions emerged.